Specific Heat Capacity of Confined Water in Extremely Narrow Graphene Nanochannels - Zhou, Runfeng; Ma, Xinyi; Li, Haoxun; Sun, Chengzhen; Bai, Bofeng (Frontiers in Energy Research, 2021)
Specific heat capacity of extremely confined water determines its performance in the heat transfer as the sizes of devices decrease to nanoscales. Here, we report the basic data of the specific heat capacity of water confined in narrow graphene nanochannels below 5 nm in height using molecular dynamics simulations. The results show that the specific heat capacity of confined water is size-dependent, and the commensurability effect of the specific heat capacity presents as the confinement decreases to 1.7 nm. The deviation of specific heat capacity of confined water with that of bulk water is attributed to the variation of configuration features, including density distribution and hydrogen bonds, and vibration features, including velocity auto-correlation function and vibrational density of states. This work unveils the confinement effects and their physical mechanisms of the specific heat capacity of nanoconfined water, and the data provided here have wide prospects for energy applications at nanoscales.